2014
DOI: 10.1136/bcr-2014-204226
|View full text |Cite
|
Sign up to set email alerts
|

Takayasu's arteritis occurring under TNF-α blockers: a new paradoxical effect?

Abstract: Takayasu’s arteritis (TA) is a rare granulomatous vasculitic disease. Recently, experimental studies and several case reports have supported the use of anti-tumour necrosis factor (TNF) therapy for severe forms of TA. We report a case of a 58-year-old woman who was followed for spondyloarthritis. Her disease was resistant to non-steroidal anti-inflammatory drugs, and TNF-α blockers were initiated. The patient developed asthaenia and severe back pain. The erythrocyte sedimentation rate was 82 mm and C reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Some authors [ 6 8 ] reported cases of TA arising under TNFi therapy and propose a causal effect of the TNFi use on TA development. Others describe aortitis occurring under TNFi therapy [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors [ 6 8 ] reported cases of TA arising under TNFi therapy and propose a causal effect of the TNFi use on TA development. Others describe aortitis occurring under TNFi therapy [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of this paradoxical side effect remains unclear and we still cannot determine the contribution of TNFi to the development of vasculitis. Nevertheless, this phenomenon might be related to immune complexes containing the drug which may be deposited on vessel walls in a disturbed immune homeostasis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 There are also reports of granulomatous large vessel vasculitis such as Takayasu arteritis. 2 Reports of TNF inhibitor-induced sarcoidosis indicate a link between TNF inhibitors and granulomatous inflammation. 3 In the central nervous system, a relationship between vascular amyloid deposits and granulomatous vasculitis has been suggested.…”
mentioning
confidence: 99%
“…10 Although anti-TNF agents are used in treatment of TA, interestingly, there are case reports of TA developing after initiation of these agents in the literature. [11][12][13] In these case reports, two patients with spondyloarthritis, one patient with rheumatoid arthritis, and one patient with Crohn's disease developed TA after treatment with anti-TNF agents. This paradoxical effect may be due to the presence of different pathophysiologic pathways in a subgroup of patients with TA.…”
mentioning
confidence: 99%